P007 Eating in alignment with the circadian clock: A strategy to reduce the metabolic impact of nightwork. (7th October 2021) - Centofanti, S; Heilbronn, L; Wittert, G; Coates, A; Dorrian, J; Kennaway, D; Gupta, C; Stepien, J; Catcheside, P; Noakes, M; Yates, C; Matthews, R; et al.
Abstract: Nightwork disrupts circadian rhythms and impairs glucose metabolism, increasing the risk for type 2 diabetes. We investigated eliminating or reducing the amount of food consumed during simulated nightwork as a countermeasure to reduce the impact of circadian disruption on glucose metabolism. N=52 healthy, non-shiftworking participants (24.4±4.9 years; 26 Females; BMI 23.8±2.5kg/m2) underwent a 7-day laboratory protocol with an 8h TIB baseline sleep, followed by 4 simulated nightshifts with 7h TIB daytime sleep and an 8h TIB recovery sleep in groups of 4 participants. Each group was randomly assigned to a meal-at-midnight (n=17, 30% energy requirements), snack-at-midnight (n=16, 10% energy requirements) or no-eating-at-midnight (n=19) condition. Total 24h energy and macronutrient intake were constant across conditions. Standard oral glucose tolerance tests (OGTT) were conducted on day2 (baseline), and day7 (recovery). Plasma was sampled at -15, 0, 15, 30, 60, 90, 120, 150 mins, assayed for glucose and insulin. Area under the curve (AUC) was the calculated. Mixed model analyses of glucose AUC found a condition-by-day interaction (p<0.001). Glucose responses to OGTT did not change with nightwork in the no-eating-at-midnight condition (p=0.219) but worsened in the meal-at-midnight (p<0.001) and snack-at-midnight (p=0.022) conditions. Insulin AUC was different by condition (p=0.047). Insulin was highest after nightwork in the no-eating-at-midnight compared to meal-at-midnight (p=0.014) but not snack-at-midnight (p=0.345). Glucose tolerance was impaired by eating-at-midnight, associated with a lower than expected insulin response. Further work is required to determine the effect of meal or snack composition as a strategy to mitigate adverse metabolic effects of nightwork.